Don't Look Back: Evidence: Under Fire # 3 - Grant, Rachel, (Novelist) ([Place of publication not identified] : Janus Publishing, 2024)
"Six months after barely escaping a nightmare, Kira Hanson is ready to take the trip of a lifetime-one she hopes will answer questions about her father's clandestine work recovering art stolen during World War II. But before she boards her flight, she's waylaid by a friend in need and finally comes face-to-face with the Navy SEAL who saved her six months ago and then ghosted her. Lieutenant Commander Randall Fallon is thrilled to cross paths with the shy art historian, but within minutes of their reunion he learns she's in danger once again. Uneasy with the idea of her embarking on a trip to track down art thieves on her own, he just might have to reprise his role as undercover bodyguard and follow her to Europe posing as an art buyer. Things heat up between Kira and Rand when he tracks her down in Malta, but it soon becomes clear that Rand's instincts were correct: Kira's digging into her father's secrets has unearthed an unexpected enemy"--.
new book 2025 summer.
Keywords: Man-woman relationships; Art thieves; Secrecy; Woman art historians; Antiquities; Bodyguards